Pengaruh Lokasi, Promosi , Pelayanan Dan Kemasan Terhadap Minat Konsumen Pada Dm Thai Tea Cikampak - Safri, Hayanuddin (Jurnal Manajemen Akuntansi (JUMSI), 2021)
The purpose of this study was to determine the influence of the influence of location, promotion, Service and packaging on consumer interest in DM Thai Tea Cikampakkecamatan Torgamba South Labuhanbatu Regency either partially or simultaneously. The sample in this study amounted to 34 people. The analysis method used is descriptive analysis, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination and this data is processed using IBM SPSS Statistics 26 program. The results of the hypothesis test showed that the partial location (X1) has a positive and significant effect on consumer interest, it is seen from the value of thitung for location is thitung 2.934 > ttable 1.697, with a significant value of 0.044< 0.05. Promotion (X2) positive and significant effect on consumer interest, it can be seen from the value of thitung for promotion (X2) is thitung 2.968> ttable 1.697, with a significant value of 0.013< 0.05. Service (X3) positive and significant effect on consumer interest, it can be seen from the value of thitung for service (X3) is thitung 2.061> ttable 1.697, with a significant value of 0.009< 0.05. Packaging (X4) positive and significant effect on consumer interest, it can be seen from the value of thitung for packaging (X4) is thitung 2.427> ttable 1.697, with a significant value of 0.025< 0.05. Ftable value in the distribution of 4: 29 is 2.70, then based on Table 4.14 it is seen that the value of Fhitung 14.244>2.70, and the significant value of 0.048< 0.05, this shows that simultaneously The Independent Variable has a positive and significant effect on the Dependent variable.